THE RELATIONSHIP BETWEEN MENSTRUAL CYCLE CHARACTERISTICS WITH DYSMENORRHEA AND ADOLESCENTS SOCIAL LIFE - Raissa Manika Purwaningtias; Dwiyanti Puspitasari; Ernawati Ernawati (UNIVERSITAS AIRLANGGA, 2020)
ABSTRACTBackground: Dysmenorrhea is a common gynecological problem related to the menstrual cycle. Risk factors for dysmenorrhea are age of menarche, length of menstrual cycle, duration and menstrual volume. Teenagers who experienced dysmenorrhea report the negative impact of dysmenorrhea on a social life. This study aimed to determine the relationship between menstrual cycle characteristics with dysmenorrhea and adolescent social life. Method: The study design used in this research was Cross Sectional with statistical analysis of Rank Spearman test and Chi Square and a significance limit of 5%. The population in this study were 449 students with the inclusion criteria of female students aged 14-16 who had menstruated in the last 3 months. Data was collected using primary data. Sample of 151 students were obtained using total sampling techniques. Results: The percentage of respondents who experienced dysmenorrhea in this study were 90.7% and 78.8% of them stated that dysmenorrhea disrupted their social life. There was a relationship between duration (p=0.006) and menstrual volume (p=0.004) with dysmenorrhea. The relationship also found between menstrual volume (p=0.033) and dysmenorrhea (p=<0.001) with adolescent social life. Conclusion: The characteristics of the menstrual cycle that were associated with dysmenorrhea were duration and menstrual volume and the social life of adolescents were significantly correlated with dysmenorrhea.